Innovative Model of Communicative Practices - Oleksiuk, Olga Mykolayivna; Bondarenko, Larysa; Cherkasov, Volodymyr; Kosinska, Natalia; Maievska, Anastasiia (Journal of History Culture and Art Research, 2019)
The article deals with the philosophical and pedagogical understanding of communicative practices in the educational process of a higher school. A typology of dialogue interaction in pedagogical search space has been proposed. Its usage creates conditions for the analysis, reflection and self-assessment of students in the organization of their training activity. The experience of organization of communicative educational clusters in higher artistic education, which provides for the transition from the primacy of formalized to innovative models of interaction between all participants of the process, has been presented. The conceptual values-semantic aspects of the implementation of interdisciplinary approach have been analyzed, and it has been shown that this approach opens qualitatively new possibilities for the reflection of the investigated object. The contours of a new view on the problem of dialogue, in particular, through the discursive activity of students, have been outlined: Problem group method, group therapy, group “buzz”, “aquarium”, and lecture-forum. The transition to interdisciplinary integration with project design forms is a prerequisite for creating an innovative model for the development of post-non-classical artistic education. In the organization of the dialogue, we take into account: the students’ method to perceive different points of view, the search for the underlying motives, that is, those problem situations through which the own style of the studied material is formed, the development of tasks-conflicts associated with higher spiritual values, ideological and semantic sphere, designing various variants of interaction ways for dialogue participants.